Clinical Implications of Immune Checkpoints and the RANK/RANK-L Signaling Pathway in High-Grade Canine Mast Cell Tumors - Talavera Guillén, Noelia C. [UNESP]; Barboza de Nardi, Andrigo [UNESP]; Noleto de Paiva, Felipe [UNESP]; Dias, Queila Cristina; Pinheiro Fantinatti, Alexandra; Fávaro, Wagner José (MDPI, 2023)
Mast cell tumors (MCTs) are the most common malignant cutaneous tumors in dogs, and they present extremely variable biological behavior. The interaction between RANK, RANK-L, and immune checkpoints is frequently detected in the tumor microenvironment, and, together, they participate in every stage of cancer development. Thus, the aim of this study was to characterize the molecular profiles of PD-L1, CTLA-4, RANK/RANK-L signaling pathway, and IFN-γ in primary tumors and lymph node metastases. Formalin-fixed, paraffin-embedded slides of MCTs and metastatic lymph nodes of ten dogs were submitted to immunohistochemical investigations. The results demonstrated that the tumor microenvironment of the high-grade mast cell tumors showed moderate or intense immunolabeling of all proteins, and the lymph node metastases also showed moderate or intense immunolabeling of checkpoint proteins. In addition, MCTs larger than 3 cm were associated with intensified PD-L1 (p = 0.03) in metastatic lymph nodes and RANK-L (p = 0.049) immunoreactivity in the tumor. Furthermore, dogs with a survival time of less than 6 months showed higher PD-L1 immunoreactivity (p = 0.042). In conclusion, high-grade MCT is associated with an immunosuppressive microenvironment that exhibits elevated RANK/RANK-L signaling and enhanced immune checkpoint immunoreactivity, potentially facilitating intratumorally immune escape. These biomarkers show promise as clinical indicators of disease progression and might response to immunotherapy in dogs with high-grade MCTs, thus emphasizing their importance for guiding treatment decisions and improving outcomes.
Keywords: dogs; immune checkpoints; immunotherapy; mast cell tumor; RANK; RANK-L